The Effectiveness Analysis Of Teacher’s Managing Class Capability On Students Learning Achievement - Riyadi, Slamet; Novaria, Novi; Prawiranegara Gani, Imam; Rais , Rinovian; Bisri Habibi , Wyeldan (Mudir : Jurnal Manajemen Pendidikan, 2023)
The objective of this study is to ascertain how the teacher's capacity to control the class affects the efficiency of student education. The research employs a quantitative approach employing descriptive techniques. It employs probability sampling, with a research sample of 70 students. The primary data collection technique employed is a survey, which is dispersed among students. To support the findings of the questionnaire data, interview methods and document studies were conducted. This research employs descriptive analysis and the classical assumption test as data analysis techniques. The findings of the study reveal that the teacher's ability to manage the class has a notable impact on the effectiveness of student learning. This is evident from the processing of data computed by SPSS via t-test statistical testing. The t-count value is greater than t-table, with a significance of 0.000. According to the test criteria t-count > t-table and if the significance is < α (0.05), H0 is rejected. The calculation of the coefficient of determination reveals that the teacher's capacity to manage the class has a positive and significant effect on the effectiveness of student learning.